COMPUTERIZED LINGUISTICS AND PSYCHOLOGY - OVERCOMING THE POLYGRAPH’S DRAWBACKS - OPHIR, Dan (Comparative Legilinguistics, 2013)
We developed an auxiliary tool, named “Software Human Reliability Estimator” (SHRE), which in certain cases can replace the polygraph. The polygraph is not always effective in measuring the reliability of a witness. For instance, the polygraph is ineffective when the witness believes that the testimony is the truth even when in reality it is not. In such cases, an alternative objective test is required. Another disadvantage of the polygraph test lies in the lack of discreetness owing to the requirement that the witness must agree to undergo a polygraph test. In addition, the polygraph test cannot be performed in real time because of its cumbersome and bulky nature. These drawbacks have motivated the search for alternatives to the polygraph. Herein, we suggest a methodology accompanied by a corresponding software package that overcomes the mentioned shortcomings of the polygraph. The methodology is based on a computer-assisted cognitive behavioral therapy methodology (CBT) (Burns 1999). CBT was originally developed for psychological treatment and can be used to characterize personalities. This methodology can also be used to find the individual’s personality disturbances and to evaluate the reliability of a witness. The CBT methodology assumes that the cognitive thoughts of a human are expressed in his language. In the literature, about ten categories of thoughts are determined, and so called distorted thoughts, indicate a behavioral deviation. Based on the above assumption, it is possible to map thoughts, including distorted thoughts and analyze them methodically with the help of linguistic tools. These tools should be able to scan the mapping and discover distorted thoughts as classified by the CBT method. We will use extreme situations as examples to illustrate distorted thoughts. The mentioned situations will refer to time description (always, never), location (everywhere, nowhere), quantity (everything, nothing, nobody), possibility (must, forced, incapable) etc. These types of expressions leave no doubt as to their meanings. The linguistic analysis is performed at two levels: semantic and syntactic. The first stage is the semantic analysis. Here, the vocabulary of the sentence is analyzed. The known linguistic term, quantitative-semantics, is given a special significance since it enables a pre-ranking of the nouns, adjectives, adverbs beyond their regular usage. Quantitative semantics analysis searches especially for superlatives such as “never”, which indicate an extreme case. This analysis is supported in the first stage by using an expression named “distinguished”. In order to find distinguished expressions it is recommended to use in the second stage of the analysis a methodology borrowed from formal-languages, a field in computer sciences. This analysis is supposed to strengthen or eliminate the indications found in the first analysis stage, the semantic analysis.